2012
DOI: 10.1002/bio.2463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure‐assisted thermal annealing on the optical properties of ZnO thin films

Abstract: ZnO thin films were prepared by the polymeric precursor method. The films were deposited on silicon substrates using the spin-coating technique, and were annealed at 330 °C for 32 h under pressure-assisted thermal annealing and under ambient pressure. Their structural and optical properties were characterized, and the phases formed were identified by X-ray diffraction. No secondary phase was detected. The ZnO thin films were also characterized by field-emission scanning electron microscopy, Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…15 Similarly, in ZnO films, PAHT promoted a significant change in the level of defects, shifting the PL emission from green to orange-yellow. 16 PAHT caused significant changes in the PL properties of CCTO 15 and ZnO 16 thin films, and it is hypothesized that a similar influence could be found in bulk α-Bi2O3. Based on these facts, this study aims to investigate the effect of PAHT on the PL properties of α-Bi2O3 needles synthesized by the microwave-assisted hydrothermal (MAH) method…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…15 Similarly, in ZnO films, PAHT promoted a significant change in the level of defects, shifting the PL emission from green to orange-yellow. 16 PAHT caused significant changes in the PL properties of CCTO 15 and ZnO 16 thin films, and it is hypothesized that a similar influence could be found in bulk α-Bi2O3. Based on these facts, this study aims to investigate the effect of PAHT on the PL properties of α-Bi2O3 needles synthesized by the microwave-assisted hydrothermal (MAH) method…”
Section: Introductionmentioning
confidence: 90%
“…Pressure-assisted heat treatment (PAHT) was successfully used to prepare calcium copper titanate (CaCu3Ti4O12, CCTO) 15 and zinc oxide (ZnO) thin films. 16 In CCTO films, PAHT caused a decrease in the band gap, moving the PL emission to a lower energy region. 15 Similarly, in ZnO films, PAHT promoted a significant change in the level of defects, shifting the PL emission from green to orange-yellow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO thin films were prepared by spin-coating deposition of a ZnO-based polymeric precursor solution on a silicon substrate followed by thermal annealing at 330°C for 32 h according to a documented method [39]. In the typical procedure, the viscosity of zinc citrate solution was adjusted at 20 cP and deposited onto substrates by spin-coating in a Model 4 00 B-6 NPP/Lite spinner, using a speed of 4000 rpm for 15 s This procedure was sequentially performed ten times for layer-by-layer deposition, and then the films were heat-treated at 350°C for 4 h in a tubular furnace to remove residual organic material, followed by annealing at 500°C for 2 h using a heating rate of 2°C/min under ambient atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain good alignment, growing order, coverage, and homogeneity, a seed layer can be prepared prior to the film growing. Among all other methods, such as spin-coating [4], sputtering [5], spray pyrolysis [6], and pulsed laser deposition (PLD) [7], electrochemical deposition (electrodeposition) offers the most efficient route to produce thin, homogenous seed layer, within low temperature. Previous works has revealed that electrodeposition method can generate uniform and reproducible ZnO layer [1,8].…”
Section: Introductionmentioning
confidence: 99%